2020
DOI: 10.1186/s12881-020-01031-z
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering genetic signatures by whole exome sequencing in a case of co-prevalence of severe renal hypouricemia and diabetes with impaired insulin secretion

Abstract: Background: Renal hypouricemia (RHUC) is a hereditary disorder where mutations in SLC22A12 gene and SLC2A9 gene cause RHUC type 1 (RHUC1) and RHUC type 2 (RHUC2), respectively. These genes regulate renal tubular reabsorption of urates while there exist other genes counterbalancing the net excretion of urates including ABCG2 and SLC17A1. Urate metabolism is tightly interconnected with glucose metabolism, and SLC2A9 gene may be involved in insulin secretion from pancreatic β-cells. On the other hand, a myriad of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…It appears that URAT1 plays a key role in urate reabsorption and in the maintenance of serum urate levels. A recent study demonstrated hypouricemia in a patient homozygous for the Trp258* (rs121907892) mutation in URAT1 despite being heterozygous for a variant of BCRP (ABCG2 Gln141Lys (rs2231142)) as well as homozygous for a mutation in NPT1 (SLC17A1 Thr269Ile (rs1165196)), both known to cause hyperuricemia [ 154 ]. In addition, four of six uricosuric agents ( Table 3 ) but only two of five hyperuricemic drugs ( Table 5 ) with available BCRP inhibition data showed clinically significant inhibition of gut BCRP, suggesting a less prominent role for gut-localized BCRP than results with Abcg2 knockout mice would suggest [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…It appears that URAT1 plays a key role in urate reabsorption and in the maintenance of serum urate levels. A recent study demonstrated hypouricemia in a patient homozygous for the Trp258* (rs121907892) mutation in URAT1 despite being heterozygous for a variant of BCRP (ABCG2 Gln141Lys (rs2231142)) as well as homozygous for a mutation in NPT1 (SLC17A1 Thr269Ile (rs1165196)), both known to cause hyperuricemia [ 154 ]. In addition, four of six uricosuric agents ( Table 3 ) but only two of five hyperuricemic drugs ( Table 5 ) with available BCRP inhibition data showed clinically significant inhibition of gut BCRP, suggesting a less prominent role for gut-localized BCRP than results with Abcg2 knockout mice would suggest [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic polymorphisms in genes purine nucleoside phosphorylase ( PNP ), adenosine deaminase, xanthine dehydrogenase/oxidase, AMPD , and 5′-nucleotidase have been also linked to altered purine biosynthesis and catabolism and immunodeficiency syndromes [3 ▪▪ ,27,28]. Many of these SNPs have also been associated with hypertension, diabetes, obesity, CVD, and neurodegenerative diseases [29,30].…”
Section: Introductionmentioning
confidence: 99%